Attacks on WSN and its Limitations - Abidin, Shafiqul; Izhar, Mohd (International Journal of Computer Sciences and Engineering, 2025)
In recent times Security has started to be the key factor in data transmission. Recent advances in networking and wireless sensing has enabled the discovery in networking and wireless sensing and has enabled the discovery of new algorithms and techniques for wireless sensor networks. A Wireless Sensor Network (WSN) comprises several sensor nodes such as magnetic, thermal, and infrared and the radar is setup in a particular geographical area. The capabilities of WSN include to manipulate and control the physical and environmental entities such as – humidity, temperature, sound, pressure, light etc. and pass this information to various other sensors present in the network in order to pass the information from the source to the sink. These wireless sensor networks have diverse applications ranging from medical care to military or educational purposes but these networks are also prone to many adversaries and attacks. Some of the most common attacks on a wireless sensor network are spoofing or replayed routing information. Certain techniques and algorithms have been introduced or developed which might not make a WSN attack-proof in all situations but may be very affective in certain situations. Selective forwarding attack is one of the most harmful attack as it can harm the complete network. A selective forwarding attack is a type of attack in which the nodes capture some data by interfering in the transmission path and steal some precious information which could be anything from secret passwords to encrypting keys and pass the rest to the destined node. The ability of capturing the required data and passing the rest of the information to the sink makes it undetectable in a network. In WSN certain techniques and algorithms have been introduced to detect selective forwarding attacks.